Temperature-Driven Variability in Candidatus Liberibacter asiaticus Titer Across Citrus Hosts, Tissues, and Seasons in Saudi Arabia - Ali A. Al Masrahi; Abdullah F. Al Hashel; Arya Widyawan; Mahmoud H. El Komy; Yasser E. Ibrahim (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Huanglongbing (HLB), caused by Candidatus Liberibacter asiaticus (CLas), continues to challenge citrus production in Saudi Arabia. Although HLB is widespread, there is still limited understanding of how temperature, season, host species, and the type of tissue sampled influence the reliability of CLas detection. In this regard, 123 CLas-positive samples sourced from major citrus-growing areas were analyzed. These samples included data from 4 major citrus species and 4 tissue types. Additionally, cycle threshold (Ct) values obtained through quantitative PCR for each sample were used to examine how climate and CLas interact in bacterial detection. As lower Ct values indicate higher bacterial abundance, an analysis of covariance (ANCOVA) was conducted to assess the influence of season, tissue type, citrus species, and average seasonal temperature on Ct values. The results demonstrated significant differences among tissue types, with petiole and midrib tissues exhibiting consistently lower Ct values. Additionally, lower Ct values were observed in spring and autumn, and higher Ct values in warmer summers and colder winters, based on average temperatures. Among the citrus species, only Citrus limon illustrated a prominent increase in CLas levels as temperatures increased. CLas levels in C. limon showed only minor fluctuations with temperature. Taken together, these results indicated that temperature gradients strongly shape CLas population levels in Saudi Arabia and influence the reliability of pathogen detection. Considering climatic context, along with tissue type and season can substantially improve sampling strategies and enhance the effectiveness of HLB monitoring programs in arid and semi-arid citrus production systems.